The Judicial Disciplinary Procedures of the New Zealand Rugby Football Union - Haggie, Maryanne (Victoria University of Wellington Law Review, 1999)
This article examines the model established by the New Zealand Rugby Football Union Inc (NZRFU) to deal with acts of violence on the rugby field. The interface between sport and the law becomes relevant when society perceives sportsfield violence as going beyond acceptable boundaries. Identifying where these boundaries lie is problematic given the traditional reluctance of both sports administrators and the courts to invoke criminal sanctions for violence in sport. Part II examines violence in rugby, the limits to the consent defence, New Zealand case law on rugby violence and the likelihood of increased court action. It looks at the debate surrounding the appropriateness of internal disciplinary tribunals for sportsfield violence, and explores the criteria sports organisations must meet to avoid criminal prosecution of their players or judicial review of their internal disciplinary decisions. Part III outlines the establishment of NZRFU procedures to deal with violence in rugby and how they operate at local, national and international levels. In Part IV, the main features of the NZRFU's judicial disciplinary procedures are reviewed. It concludes that the NZRFU has created an effective and fair set of disciplinary rules to deal with violence in rugby, which has been extended to international competitions. However, there are some problems in its application. It will be suggested that changes could be made to the NZRFU's internal disciplinary procedures to improve consistency and independence and ultimately demonstrate to the rugby community, the courts and the public that violence in rugby is decreasing.